If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(5x + -6) = 108x Reorder the terms: 9(-6 + 5x) = 108x (-6 * 9 + 5x * 9) = 108x (-54 + 45x) = 108x Solving -54 + 45x = 108x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-108x' to each side of the equation. -54 + 45x + -108x = 108x + -108x Combine like terms: 45x + -108x = -63x -54 + -63x = 108x + -108x Combine like terms: 108x + -108x = 0 -54 + -63x = 0 Add '54' to each side of the equation. -54 + 54 + -63x = 0 + 54 Combine like terms: -54 + 54 = 0 0 + -63x = 0 + 54 -63x = 0 + 54 Combine like terms: 0 + 54 = 54 -63x = 54 Divide each side by '-63'. x = -0.8571428571 Simplifying x = -0.8571428571
| 2x(3x+5xy)= | | -27=7x-6 | | 80=47.6r+8 | | 12x-4=11x+19 | | n+11=-81 | | ln(y)=-5*x+ln(c) | | =7(y+3) | | x-9+3(5x+4)=2(x+6) | | 3x(x-6)-(10x-6)= | | 3(-3x+2)=-7(x+3)-2 | | x^2-3-y=0 | | 0.25(x+2)-5=12 | | (10y+6)-(17y+8)= | | x^2+100x=0 | | (y^2+2y)(y^3-2y^2+1)= | | 5=20x+(10x*x) | | -2=0.2-6 | | 6x-4=23-3y | | x^2+12x+9=4 | | 3x-2=7x-3 | | 3a+5b=b+7b | | X+3=-12+6x | | 6(5x-11)=48x | | .25+X=45 | | 7m=2+5m | | -73=3e | | 10=-2x-2(-4x+4) | | 2(2w+3x)-3(2w-3x)= | | T(x)=19-(-3) | | 9m=-30+3m | | 4x+4+2x=9x+1 | | Y=7(x+1) |